Shifting Patterns of BMI and Skinfold Fatness among US Children: 1985/87 vs. 2012 (Epidemiology, Biostatistics, and Public Health, 2022)
Background: Childhood obesity has been recognized as a major public health concern. The purpose of this study was to determine specific shifting patterns of BMI and skinfold fatness across different age and sex groups between 1985/87 and 2012.Methods: The data of 9,366 children aged 8-15 years from two nationally representative surveys, i.e., 1985/87 National Children and Youth Fitness Study I & II and 2012 National Health and Nutrition Examination Survey National Youth Fitness Survey, were analyzed. Specifically, changes of BMI-based obesity prevalence and shifting patterns of BMI, height, weight, skinfold body fat percentage (skinfold-fat%), subscapular skinfold, and triceps skinfold from 1985/87 to 2012 were estimated by age and sex using the 1985/87 quartiles as the baseline.Results: Significantly increased obesity prevalence were reconfirmed for both boys (12.12%, P